Implementation of Pragmatism and Contructivism Philosophical Thinking in the Educational Institution of Vocational School 15 Merangin - Nifriza, Ifna; dari, diana wulan; Rifma, Rifma; Syahril, Syahril; Jasrial, Jasrial (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
ABSTRACTThe purpose of this writing is to examine the theory of pragmaticism and constructivism which is implemented in educational institutions in general and implemented in vocational high school educational institutions, SMKN 15 Merangin, Jambi Province in particular. Education can be said to be one of the life experiences that makes individuals have broad insight or knowledge, because with education humans can think by changing their thinking patterns to become better.The research method used islibrary research through several researches and writings in the form of books, theses and articles from journals, and also collection techniques The data uses observations and photo documents.The theories of pragmatism and constructivism can be applied in learning methods that use direct activities for students. So, from this research, the problem formulation can be drawn on how to implement the theories of pragmatism and constructivism in vocational high school educational institutions, SMKN 15 Merangin.